Deep Breathing Spiritual Therapy to Reduce Pre-Circumcision Anxiety in Children in Sukoreno Village, Jember Regency: Terapi Spiritual Deep Breathing Untuk Menurunkan Kecemasan Pra-Khitan Pada Anak Di Desa Sukoreno Kabupaten Jember - Kushariyadi; Rondhianto (DEDIKASI SAINTEK Jurnal Pengabdian Masyarakat, 2022)
Health problems in the community in Sukoreno Village, Jember Regency, namely children feeling anxious and even afraid when circumcision is about to be performed. This is because children receive information from their friends which makes fear worse for no apparent reason. The family, especially the parents, also have difficulty dealing with these problems so they don't know how to handle them. Parents have never known about deep breathing spiritual therapy and its benefits in preventing or reducing anxiety and fear, especially in children who will be circumcised. The aim is to provide education or health counseling regarding deep breathing spiritual therapy to reduce anxiety in children who are about to be circumcised in Sukoreno Village, Jember Regency. Using the education or health counseling stage method, namely the orientation, work, and termination stages. Using the leaflet instrument as an extension tool. The results of the service are providing education about the meaning of deep breathing spiritual therapy, the goals and benefits of therapy, indications for therapy, benefits of therapy, mechanisms of therapy, and things that need to be considered in therapy. There were 20 children who attended. The conclusion of this dedication is that deep breathing spiritual therapy is useful in reducing anxiety in children who will be circumcised.